Climate Action for Health: An Urgent Call from the Global Cardiovascular Community - Fausto J. Pinto; Kelcey Armstrong-Walenczak; Karen Sliwa (Ubiquity Press, 2021)
The current and immediate past Presidents of the World Heart Federation are pleased to publish this invited editorial to demonstrate the organization's strong, ongoing commitment to addressing the impacts of air pollution on cardiovascular health and outline its strategy for action.